Has Chinese Aid Benefited Recipient Countries? : Evidence from a Meta-Regression Analysis - Mandon, Pierre (IMF Working Papers; Working Paper ;, 2022)
This paper employs a meta-regression analysis of 473 estimates from 15 studies to take stock of the empirical literature on Chinese aid effectiveness. After accommodating publication selection bias, we find that, on average, Beijing's foreign assistance has had a positive impact on economic and social outcomes in recipient countries but an opposite effect on governance, albeit negligible in size. We also show that (i) studies that fail to uncover statistically significant effects are less likely to be submitted to journals, or accepted for publication; and (ii) results are not driven by authors' institutional affiliation. Differences in study characteristics such as the type of development outcome considered, how the Chinese aid variable is measured, the geographic region under study, and publication outlet explain the heterogeneity among Chinese aid effectiveness estimates reported in the literature.